Malformations in the offspring of women with thyroid cancer treated with radioiodine for the ablation of thyroid remnants - Rosário,Pedro Weslley S. do (2006)
RATIONALE: Since ovarian function is only temporarily compromised by radioiodine therapy, many women with thyroid cancer treated with radioiodine can become pregnant. The present study evaluated the evolution of these pregnancies and the consequences for the offspring. PATIENTS AND METHODS: We retrospectively analyzed 78 pregnancies of 66 women submitted to total thyroidectomy, followed by radioiodine therapy (3.75.5 GBq 131I, mean 4.64 GBq). In all patients, conception occurred one year after ablative therapy (mean of 30 months). Age ranged form 19 to 36 years (mean of 30.6 years) at the time of radioiodine treatment and from 23 to 39 years (mean of 32.8 years) at the time of conception. RESULTS: Four (5.1%) of the 78 pregnancies resulted in spontaneous abortions. Three (4%) of the 74 deliveries were preterm and there was no case of stillbirth. The birthweight was > 2500 g in 94.6% of the children (mean ± SD: 3350 ± 450 g) and only one infant (1.3%) presented an apparent malformation at birth (intraventricular communication). No difference in the age at the time of radioiodine therapy or conception or in radioiodine dose was observed between pregnancies with an unfavorable outcome and those with a favorable outcome. CONCLUSION: We conclude that pregnancies that occur 12 months after ablative therapy are safe.